PERAN TEKNIK DASAR DALAM PEMBINAAN PRESTASI BOLA VOLI: SEBUAH KAJIAN LITERATUR - Natasya Sormin; Azhar Fadillah Nasution; Gilang Pratama; Andra Zerovaro Ginting; Farhan Qalbi; Deni Rahman Marpaung; Randi Kurniawan (STKIP Subang, 2026)
Volleyball is one of the most popular team sports in Indonesia and has a prominent place in physical education curriculum at all school levels. However, many players and students still face difficulties in mastering basic techniques such as passing, serving, and spiking. This literature review aims to examine the role of basic technique mastery in volleyball performance development, drawing from various national and international studies. The review covers three main aspects: the importance of basic technical skills, common errors found in each technique, and recommended training approaches to improve them. The findings consistently show that solid mastery of basic techniques is the primary foundation of volleyball performance. Passing errors, particularly in forearm passing, remain the most frequently reported technical problem, followed by inconsistent serving and poor spike timing. Training approaches that combine repetitive drill methods with game-based learning show promising results across age groups. This review provides practical insights for physical education teachers and volleyball coaches in designing effective and structured training programs.